Un approccio fenomenologico esistenziale e della psicoterapia della Gestalt al lavoro con pazienti che soffrono di attacchi di panico - Mirko Antoncecchi, Paola Chiantera, Damiano Conte, Maurizio Daggiano, Mariangela De Fabrizio, Elisa Anna De Giorgi, Elide del Piano, Amalia Giordano, Franco Mongiò, Chiara Musio, Milena Perulli, Silvia Sammarco, Renata Zuma, Caterina Terzi, Alexander Lommatzsch (Marp Edizioni, 2020)
The authors propose a phenomenological/existential approach in psychotherapeutic intervention on panic attacks. From the observations in the psychotherapeutic settings emerges the tendency of the patient with a panic attack symptom not to take clear and defined positions in his emotional and professional life, the tendency to say "yes" rather than "no", even in situations where he is not convinced of his choice. Others do not consider him a credible interlocutor where choices have to be made, but a person who always adapts. He tends to have low self-esteem, does not believe in his abilities and does not express his opinions for fear of being judged and ridiculed. Exploring the experiences of those who suffer from panic attacks opens up the hypothesis that panic attacks, more than as a symptom related to the sphere of anxiety and fear, is a manifestation of existential/relational distress with respect to inadequate anger management. Anger becomes unexpressed and repressed (retroflexion) as a result of the accumulation of dissatisfactions, frustrations and deprivations to which the patient cannot say "no". When the person is in a situation where they feel compelled to do something they don't want to do, and they don't know how to disengage, anxiety intervenes which can increase to the point of developing various symptoms of panic. In this proposed study we will look at the extent to which unexpressed anger can affect panic attacks. The assumption behind the gestalt practice is that a person experiences anger when he or she does not get what he or she wants, or when he or she is in a territorial conflict. Hence the different acts of the person in the manifestation of anger.